Vulnerable Integrity: Theological-Ethical Reflections on Human Integrity and Integrity Violations - Ott, Tabea (De Ethica, 2023)
This paper presents a social-theologically informed interpretation of the term integrity, as it occurs in fundamental law. It explores the manifestations of integrity violations and proceeds to draw an inference: an integrity violation can directly emanate from a misconception regarding integrity itself, as well as the implementation of protective measures that follow it. Integrity in its wholeness dimension is understood as open-endedness and non-seclusion rather than as a substantial, clearly definable characteristic of a person. This open-endedness and non-seclusion results from the relational constitution of an individual. Consequently, it follows that a violation of integrity occurs when the open-endedness and non-seclusion of a person and their relational Becoming is hindered. The new definition of integrity is particularly important when it comes to the governance of new health technologies, especially Digital Twins that can become representatives of a person. Human integrity is non-violated only when it is understood as open to relational Becoming and this Becoming shows its expression in the mutual enabling and support of self-articulation.